Ethics Beyond Transparency: Resisting the Racial Injustice of Predictive Policing. - Sheehey, Bonnie (Techné: Research in Philosophy & Technology, 2020)
This paper responds to recent work highlighting the problematic racial politics of predictive policing technologies. Drawing on Michel Foucault’s account of ethics as counter-conduct, I develop a set of ethical techniques for resisting the racial injustice at work in predictive policing. This framework has the advantage, I argue, of not reducing the ethical issues of predictive policing solely to epistemic concerns of transparency. What I suggest is that we think about the ethics of technology less as an epistemic problem than as a problem for action or practice. By thinking of ethics in terms of resistant practices, we can begin to consider a notion of responsibility that holds us and the technologies we bind ourselves to accountable for the harms created by this bond.